A SOCIO-INTERACTIVE THEATER AS A SOCIAL-PSYCHOLOGICAL METHOD FOR DE-STIGMATIZATION OF PEOPLE WITH INTELLECTUAL DISORDERS - Palamarchuk, Mikhail (PSYCHOLOGICAL JOURNAL, 2020)
The article presents the phenomenon of social stigma as a condition that significantly affects life quality of various social groups, including people with intellectual disabilities. The general social significance of research on social stigma is noted in order to find means of influencing it. The phenomenon of social de-stigmatization as one of the conditions for steady society development is considered; the peculiarities of work with social stigma are presented; the definition of de-stigmatization and the possible stages and forms of its implementation are given. An inclusive social-interactive theater is presented as a method changing general public’s perceptions of other social groups, on the example of people with intellectual disabilities. The boundaries and possibilities to use an inclusive social-interactive theater as a special educational technique representing the problems faced by representatives of different social groups, as well as the characteristics and needs of the represented social group were investigated. Representatives of a stigmatized group were the actors at the organized social- interactive theater. The ideas of general public (people without intellectual deficiencies) about people with intellectual disabilities were studied. The respondents’ views and assessments regarding the implementation of their own rights, as well as the specifics of the implementation of intellectual disabled people’s rights in Ukraine were analyzed. The dynamics of the theatre audience’s representations and psychoemotional states were statistically determined in connection with the performance of the social-interactive theater providing information on the implementation of intellectual disabled people’s rights, their experiences and personal stories of the actors-representatives of the examines social group. We concluded that the information about a social group presented using the theatrical method influence favorably on audience and actors and support audience’s positive transformations; improve their knowledge about the group, namely, about the rights of social group representatives and about their possible characteristics.